PERBANDINGAN MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) DENGAN MODEL PEMBELAJARAN INQUIRY TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA PADA MATERI GAYA - Anggie Yulisdiva; Cecep Sodikin; Poppy Anggraeni (JESA-Jurnal Edukasi Sebelas April, 2023)
The background of this research is to compare the RADEC model with the inquiry model on the higher order thinking skills of elementary school (SD) students. The purpose of this study was to find out which higher order thinking skills were better using the RADEC learning model than those who studied with the style material inquiry learning model. The method used is a pre-experimental method with a quantitative approach with a one shot case study research design. The sample in this study were all fourth grade students at SDN Cijambu II. Class A collects 20 students using the inquiry model and class B collects 20 students using the RADEC model. The data collection technique in this study is a test technique used after learning takes place (posttest) to see higher-order thinking skills. The results showed that t_count = 3.137 and t_table = 2.024. So t_count > t_table, then H0 is rejected and Ha is accepted so that there are differences in students' higher-order thinking skills using the RADEC model with the inquiry model. Based on the average posttest results, the RADEC model scored (75.50) while the inquiry model (59.50). The higher-order thinking skills of students who use the RADEC learning model are better than the high-order thinking abilities of students who study with the inquiry learning model in style material in class IV SDN Cijambu II, Tanjungsari District, Sumedang Regency, in the 2021/2022 academic year.